Human resources for health coordination mechanisms: lessons from Bauchi and Cross River states of Nigeria. (13th April 2021) - Okech, M; Okoroafor, S C; Mohammed, B; Ojo, O
ABSTRACT: Background: Addressing the challenges of the health crisis requires collaboration by multiple sectors and stakeholders with a complementary role in a single platform that coordinates policy and programs relating to the health workforce for sustainability. Methods: Information from purposefully selected stakeholders involved in human resources for health programs in two selected states of Nigeria was collected during a workshop attended by 60 participants drawn from government, multilateral agencies, the private sector, bilateral agencies, academia, professional associations, and regulatory bodies. Results: Lessons learnt from Bauchi and Cross River states HRH platforms included successful joint planning and implementation human resources for health strategies that significantly mobilized resources and improved performance. Human resources for health coordination platforms with strong governance structures are sustainable. Conclusion: The coordination platforms require governance structures for inter-sectoral coordination and collaboration. This enhances joint planning, implementation and monitoring of HRH activities.